LINGUISTIC INTERFERENCE IN CONTACTING LANGUAGES OF GERMAN-RUSSIAN BILINGUALS - Baykova, Olga; Bukharov , Valeriy; Porchesku , Galina (Revista Inclusiones, 2020)
Modern linguistic studies give a lot of attention to the issue of language forms. It is especially concerned with the multi-factor description of the forms of existence of a language associated with different territories. These forms represent relatively autonomous languages which have their specific features, norms and speakers. The dialects of the Russian Germans of the Kirov region are transmigratory; they are often described as disappearing dialects of the German language – a kind of a supra-regional form of the language. The relevance of their study results from the linguistic significance of language interaction at the present stage of development of the German language in Russia, where it has developed and modified in the conditions of language enclaves for many decades